Can hydrological niche segregation explain species distributions in an aquifer-dependent wetland? - Havhi, Mpho (Department of Biological Sciences, 2025)
Aim: To investigate post-fire succession in fynbos wetland plant communities, test whether these species segregate along fine-scale hydrological gradients and to identify species potentially most sensitive to groundwater abstraction. Intro: Hydrological gradients, which form between permanently inundated wetlands and adjacent dry habitats, are key drivers of vegetation community composition and structure, promoting opportunities for adaptive speciation and community coexistence. In the seasonally arid fynbos region of South Africa, the occurrence of permanently inundated, groundwater-fed wetlands suggests that fine-scale hydrological gradients may significantly shape floristic diversity in this region. The extent to which fine-scale hydrological gradients influence community composition and species segregation requires further testing in fynbos but has important implications for understanding the potential impacts of groundwater abstraction in these fire-prone systems as well as identifying potentially sensitive species. Methods: I analyzed plant community composition and abundance data, along with soil volumetric water content collected across three transects in an aquifer-fed wetland, from 2011 to 2022. Non-parametric multivariate tests were used to quantify spatial and temporal changes in community composition, highlighting general patterns of community clustering across transects and changes related to post-fire succession. The hydrological niche space was quantified across an aquifer-dependent wetland by representing soil moisture data along two hydrological axes: the sum of exceedance values for flooding (SEVa) and drought (SEVd). Using a subset of persistent species, species locations were fitted to these hydrological axes based on their proximity to soil moisture probes. Species were ranked in accordance with their position on this gradient, indicating a preference for flooded or drier sites on the wetland. Results: Successional changes were observed in the vegetation at different ages post-fire as well as shifts in early post-fire community composition between fire events. A robust test of the hydrological niche concept using several species that persisted over the post-fire successional trajectory shows that wetland community composition is spatially structured along hydrological gradients. It was also determined that species display some degree of hydrological niche segregation, with preference for either waterlogged or dry niches within the wetland. Discussion: The results suggest that species segregate along hydrological gradients defined by the number of days under flooding and dry conditions and can thus be ranked according to their preference for inundated or dry hydrological niches. The occurrence of several species with a strong preference for, or dependence on, permanently inundated niches, highlights the potential impacts of groundwater abstraction on species composition, abundance and distribution, which may affect this hydrological niche. The study takes proactive steps in monitoring ecologically sensitive ecosystems before groundwater abstraction, to ensure that appropriate vegetation management and conservation strategies are in place and can be implemented when necessary.